Pengembangan LKPD Berbasis Praktikum pada Pembelajaran IPA di Madrasah Tsanawiyah - Roza, Media; Chania, Rahmi (Universitas Islam Negeri Imam Bonjol Padang, 2018)
This study aims to: (1) produce practicum worksheets (LKPD) development products on science learning in Madrasah Tsanawiyah (2) produce practicum based LKPD on science learning with valid, practical and effective product quality. This research is a research and development (R & D) research with 4-D models by Thiagarajan and Sammel. The results of this study are: (1) produced practicum-based LKPD in second semester science VIII science learning. (2) the average value of product validity from all aspects 91% with a very valid category. The product practical value is 88% with a very practical category. And the average value of product effectiveness is 86% with a very effective category to increase students' interest in learning science.